(untitled) (Argos, 2025)
Euripides’ Medea is an exceptional tragedy, not only its content but also its formal aspect, both in regard to the whole play and the individual parts. Among these, the prologue stands out, which is an element that is perfectly integrated and in harmony with the whole, while by itself it is a "perfect" piece and very rich in all kinds of issues: with an extremely careful composition and full of content from different perspectives: mythical, psychological, social, daily life, characters and their portrayals.